2002
DOI: 10.1001/archinte.162.12.1333
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Left Ventricular Hypertrophy After Exercise and Weight Loss in Overweight Patients With Mild Hypertension

Abstract: In a cohort of overweight, sedentary men and women, exercise and weight loss reduced blood pressure and induced favorable changes in left ventricular structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 37 publications
4
29
1
2
Order By: Relevance
“…The effect of weight reduction on LV geometry and mass through diet control and exercise programs was reported to be minor and even variable (7,31). The relatively small magnitude of weight loss in these programs may explain this result.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of weight reduction on LV geometry and mass through diet control and exercise programs was reported to be minor and even variable (7,31). The relatively small magnitude of weight loss in these programs may explain this result.…”
Section: Discussionmentioning
confidence: 99%
“…e effects of exercise training on cardiac remodeling in hypertensive human subjects have been reviewed elsewhere [63] and have shown equivocal results with some studies showing no change in le ventricular mass [64][65][66][67][68][69], a decrease in le ventricular mass/le ventricular mass index [64,[70][71][72][73][74], and an increase in le ventricular mass/le ventricular mass index [5,66]. e majority of these studies showed that systolic and diastolic blood pressure was reduced following exercise, and imaging was most oen measured with M-mode and 2D guided echocardiography.…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…The mechanism of reduction in muscle mass in myocardium by ACE inhibitor treatment is thought to be due to inhibition of myocardial fibrosis thereby reversing hypertrophy (Crisman et al 1985) . The effect of exercise on muscle mass in hypertension is controversial with various studies indicating both hypertrophy as a result of exercise (Barnard, et al 1980) and a reduction in hypertrophy (Hinderliter, et al 2002). There were others however, indicating no significant change in muscle mass due to exercise (Bersohn and Scheuer 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that moderate exercise in humans reduces left ventricular hypertrophy (Himeno, et al 1996;Hinderliter, et al 2002) . Moderate exercise has been shown to also induced myocardial capillary growth in the spontaneously hypertensive rat (Crisman et al 1985).…”
Section: Introductionmentioning
confidence: 99%